Polysiloxane-polyurethane rigid foam and preparation method thereof

By using an alcoholamine composition containing ethanol isopropanolamine and ethanol diisopropanolamine and a foaming agent containing polysiloxane diol and other ingredients, the problem of low adhesion strength of polyurethane foam during the spraying process is solved and achieved The mechanical strength and thermal insulation properties of the foam are improved.

CN119350573APending Publication Date: 2025-01-24SHANDONG UNIV OF TECH +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202310910392.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When using aqueous alcohol amine compositions as the foaming agent, the prior art causes the polyurethane foam to have low adhesion strength during spraying, easy peeling, and unstable foam size, affecting thermal insulation performance.

Method used

An alcoholamine composition containing ethanol isopropanolamine and ethanol diisopropanolamine is used as a foaming agent, and polysiloxane diol and silane coupling agent are added to the polymer polyol composition to improve the mechanical properties of the foam. strength and bonding strength.

Benefits of technology

It improves the initial adhesion strength and curing strength between the polyurethane foam and the substrate, avoids foam peeling and delamination, and enhances the mechanical strength, hydrolysis resistance and thermal stability of the foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350573A_ABST
    Figure CN119350573A_ABST
Patent Text Reader

Abstract

The invention relates to polysiloxane-polyurethane rigid foam and a preparation method thereof. The preparation method comprises the following steps: mixing polyisocyanate and a polymer polyol composition, and spraying and foaming, (I) 100 parts by weight of a polymer polyol comprising: 1) 50-60 wt% of a sucrose starting polyether polyol; 2) 20 to 25 wt% of a polysiloxane diol; 3) 12 to 18 wt% of a sorbitol starting polyether polyol; 4) 5 to 10 wt% of a polycarbonate polyol; 5) 0.5-4 wt% of a silane coupling agent containing a hydroxyl group or an amino group; (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer; (III) 0-18 parts by weight of a flame retardant; (III) 8 to 16 parts by weight of ethanol isopropanolamine and ethanol diisopropanolamine carbonate (AC) as a foaming agent. The foam has good mechanical strength, bonding strength to a base material, thermal stability and weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polysiloxane-polyurethane rigid foam and a preparation method thereof, and also relates to a polymer polyol composition (white material) for foaming containing a carbonate organic alcohol amine salt foaming agent and a polymer polyol, wherein the composition is used for preparing a weather-resistant and hydrolysis-resistant spray-coated rigid polyurethane foam, and is particularly used for winding and spraying the rigid polyurethane foam on the outer surface of a stainless steel pipe or spraying on a stainless steel plate. Background Art

[0002] Polyurethane rigid foam material is a high-quality thermal insulation material, widely used in refrigerators, freezers, water heaters, cold chain insulation and other industries. At present, in the field of building exterior wall (concrete) spraying and stainless steel pipe winding spraying, people have higher and higher requirements for energy saving and carbon reduction. Therefore, the selection of environmentally friendly foaming agents for the preparation of polyurethane insulation materials in this field is becoming more and more stringent. The use of environmentally friendly chemical foaming agents is currently a very good choice.

[0003] At present, the application range of PU spray foaming is relatively wide. Generally, the polyurethane rigid foam material formed by spraying is prepared by mixing and spraying a polymer polyol composition (white material) with a polyisocyanate (black material), reacting and curing, wherein the white material contains a major portion of polyether polyol and a minor portion of a polymer polyol of aromatic polyester polyol (e.g., polyethylene phthalate polyol) and / or toluene diamine polyether polyol, and contains auxiliary agents such as a blowing agent, a catalyst, and a foam stabilizer.

[0004] US6326412 B1 discloses ammonium carbamate as a polyurethane foaming agent, wherein the viscosity of the ammonium carbamate is as high as 2200 mPa.s (see lines 51-55 in column 6 of the specification), and the ammonium carbamate is in a viscous or semi-solid state.

[0005] When water is used as a foaming agent to prepare PU foam, only open-cell PU soft foam can be prepared. At present, in the case of using a composite foaming agent containing more water, for example, in a foaming agent composed of water and cyclopentane or in a foaming agent composed of water and a hydrofluorocarbon physical foaming agent, if the amount of water used is large, the formed polyurethane foam has a high open-cell rate, its size is unstable (prone to shrinkage and deformation), and its thermal insulation performance will decrease.

[0006] In addition, in the spraying process of polyurethane foam, the white material (polymer polyol component A) and the black material (isocyanate component B) are usually mixed by a sprayer (and then sprayed on the surface of a substrate (such as a steel plate, a steel pipe, or a concrete structure such as a wall) through a spray gun. Generally, spray foaming is carried out in a spraying manner of 2-3 cm per layer and a total thickness of 20-30 cm. The foam is then formed and solidified to obtain a polyurethane rigid foam as a thermal insulation material layer. If a hydrate of a carbonate alcohol amine salt with a higher activity or a higher CO2 content is used as a component of a foaming agent for spraying polyurethane foam, it is found that the foam rises too quickly in the early stage of the foaming reaction, the wet foam expands and rises rapidly, and the surface layer of the foam quickly crusts and solidifies.

[0007] However, the bonding strength between the substrate and the foam or between two adjacent foam layers decreases (due to foam shrinkage), and as a result, the (subsequent) polyurethane coating sprayed on the substrate or sprayed on the cured polyurethane foam coating often cracks or peels off from the substrate or from the cured polyurethane foam layer (i.e., delamination between adjacent foam layers).

[0008] In addition, in the prior art, aqueous alcohol amines (e.g., carbonates of primary amine alcohol amines (e.g., ethanolamines), and carbonates of some secondary amine diol amines, e.g., carbonate di(diethanolamine) salts, etc.) are used as foaming agents. These alcohol amines have a greater influence on the urethanization reaction between the polymer polyol composition (white material) containing an amine catalyst and polyisocyanates (black material). In particular, some amine foaming agents affect the catalytic action of the amine catalyst, e.g., causing an excessively fast reaction speed in the early stage and insufficient curing reaction in the later stage, affecting the strength of the foam material, and causing the foam material to be dimensionally unstable (high opening rate, easy to shrink and deform). In addition, when aqueous alcohol amines (e.g., triethanolamine hydrate) are used as foaming agents for preparing a spray-coated polyurethane rigid foam with a relatively large thickness, during the spraying process, because the reaction speed is relatively fast and heat is quickly released, a "core burning" phenomenon occurs inside the foam material, which reduces the thermal insulation performance of the foam material, and even causes the foam material to crack from the substrate to form cracks or to delaminate between two adjacent foam layers to form cracks.

[0009] In addition, US2622099A, US4169856A, US2051486A, GB448373A, GB710861A, GB1387573A, GB642950A, GB760215A, GB655580A and CA1003358A disclose isopropanolamine, ethanolamine or butanolamine prepared by the reaction of aqueous ammonia with propylene oxide or ethylene oxide.

[0010] CN107663157A and CN103435499A disclose methods for producing ethanol diisopropanolamine by reacting ethanolamine with propylene oxide, but do not disclose that the product can be used as a PU foaming agent.

[0011] CN114805902A discloses a chemical-physical combined carbonate alcohol amine salt foaming agent composition for use in the preparation of cast polyurethane rigid foam, which comprises: 1) a carbonate alcohol amine salt chemical foaming agent (F1) with a high water content and a low bicarbonate content; and 2) cyclopentane; 3) an optional physical foaming agent (F2) with a boiling point in the range of 15-41°C, wherein the physical foaming agent (F2) is selected from one or more (two or three) of HFC-245fa, HFC-365mfc, LBA and hexafluorobutene; wherein the chemical foaming agent (F1) comprises: A) 67-90wt% of di(C2-C9 alcohol amine) carbonate; B) 10-33wt% of water; C) 0-20wt% of C2-C9 alcohol amine.

[0012] CN109422913A discloses a foaming agent comprising a polyamine salt and a propanolamine salt and use thereof in a polyurethane refrigerator-freezer foam material.

[0013] CN109422903A discloses a foaming agent comprising a secondary amine salt and a propanolamine salt and use thereof in a polyurethane refrigerator-freezer foam material.

[0014] The foaming agents disclosed in the above documents CN114805902A, CN109422913A and CN109422903A are used for pouring foaming, but have poor effects or cannot be used in spraying polyurethane foaming.

[0015] When using the prior art CO2- and water-containing amine composition (AC) and the prior art combined polyether (polymer polyol composition) for spray foaming, the problems often encountered are: the initial adhesion strength between the sprayed PU foam layer and the substrate (for example, steel, such as steel plate or steel pipe) or concrete substrate is low, the wet foam sprayed at the usual spraying speed often peels off and falls off the substrate, and the bonding strength after the foam is cured is low, peeling occurs between the foam and the substrate after the foam is cured, or delamination occurs between adjacent foam layers.

[0016] In addition, for polyurethane foams used in the wild or outdoors (such as insulating polyurethane foams on the outer surface of oil or natural gas pipelines or on stainless steel plates), how to improve their mechanical strength, hydrolysis resistance, thermal stability and weather resistance remains a difficult problem. Summary of the invention

[0017] In order to solve the technical problems existing in the prior art, the inventors of the present application firstly provide an aqueous alkanolamine composition (AC) (or referred to as an aqueous alkanolamine mixture or an alkanolamine hydrate) comprising ethanol isopropanolamine and ethanol diisopropanolamine for polyurethane foam spraying, wherein the composition is suitable for preparing rigid polyurethane foam by spraying as a foaming agent.

[0018] The freezing points (melting points) of diisopropanolamine and triisopropanolamine are 42° C. and 45° C., respectively, and at room temperature, diisopropanolamine and triisopropanolamine are white crystals or solid powders, which indicates that symmetrical diisopropanolamine and triisopropanolamine have a strong tendency to crystallize or associate.

[0019] The inventors of the present application obtain an alcoholamine composition (AC) by combining ethanol isopropanolamine with ethanol diisopropanolamine of asymmetric structure, and reduce the crystallization tendency of the alcoholamine composition (AC) by utilizing the mutual doping effect between the two, so as to obtain an aqueous alcoholamine composition (AC) that does not crystallize or solidify (with a not too high viscosity) at ambient temperature (e.g., 5-40° C.). Therefore, the foaming agent (AC) is suitable for use as the main or only foaming agent to prepare a rigid polyurethane foam layer on a substrate (stainless steel or concrete).

[0020] In order to ensure that the alcoholamine composition (AC) of the present invention does not crystallize, does not solidify and has a lower viscosity, it is desirable not to add structurally symmetrical diisopropanolamine and triisopropanolamine to the alcoholamine composition (AC) as much as possible.

[0021] In order to improve the mechanical strength, hydrolysis resistance, thermal stability and weather resistance of polyurethane foam used in the wild or outdoors, the inventor of the present application provides a foaming polymer polyol composition for preparing polyurethane rigid foam, that is, a polyurethane foaming white material. By using polysiloxane diol and silane coupling agent in the foaming polymer polyol composition, the mechanical strength, bonding strength to the substrate, hydrolysis resistance, thermal stability and weather resistance of the foam can be improved.

[0022] In addition, by using an alcohol amine composition (AC) containing a specific amount of CO2 and water, the initial adhesion strength between the sprayed PU foam layer and the substrate (for example, steel, such as a steel plate or a steel pipe) or a concrete substrate is improved (the sprayed wet foam does not fall off the substrate at a normal spraying speed) and the curing strength (no peeling occurs between the foam and the substrate after the foam is cured, or no delamination occurs between adjacent foam layers).

[0023] According to a first aspect of the present invention, there is provided a polysiloxane-polyurethane rigid foam, which is formed by mixing and spraying a polyisocyanate with a polymer polyol composition, wherein the polymer polyol composition comprises or consists of the following components:

[0024] (I) 100 parts by weight of a polymer polyol comprising: 1) 50-60 wt% (preferably 52-58 wt%, more preferably 54-56 wt%, for example 55 wt%) of a sucrose-initiated polyether polyol (preferably sucrose-initiated polyoxypropylene polyol) having a hydroxyl value in the range of 290-450 mgKOH / g (preferably 300-440 mgKOH / g, more preferably 310-430 mgKOH / g, such as 320, 330, 350, 370, 400, 410, 420); 2) 20-25 wt% (preferably 20-30 wt%) of a sucrose-initiated polyether polyol (preferably 20-30 wt%) of a sucrose-initiated polyoxypropylene polyol) having a hydroxyl value in the range of 290-450 mgKOH / g (preferably 300-440 mgKOH / g, more preferably 310-430 mgKOH / g, such as 320, 330, 350, 370, 400, 410, 420); 2) 12-18 wt% (preferably 13-17 wt%, for example 14-16 wt%) of polysiloxane diol (e.g. polydimethylsiloxane diol) having a hydroxyl equivalent weight (HEW) in the range of 400-600 g / mol (preferably 420-580 g / mol, preferably 440-560 g / mol, preferably 450-550 g / mol, preferably 460-540 g / mol, preferably 470-530 g / mol, preferably 480-520 g / mol, preferably 500-510 g / mol); 3) 12-18 wt% (preferably 13-17 wt%, for example 14-16 wt%) of polysiloxane diol (e.g. polydimethylsiloxane diol) having a hydroxyl equivalent weight (HEW) in the range of 400-600 g / mol (preferably 420-580 g / mol, preferably 440-560 g / mol, preferably 450-550 g / mol, preferably 460-540 g / mol, preferably 470-530 g / mol, preferably 480-520 g / mol, preferably 500-510 g / mol); , 15, 16wt%) of sorbitol-started polyether polyol (preferably sorbitol-started polyoxypropylene polyol), whose hydroxyl value is in the range of 340-520mgKOH / g (preferably 350-490mgKOH / g, such as 360, 370, 380, 400, 450, 470, 500); 4) 5-10wt% (preferably 6-9wt%, such as 7, 8wt%) of polycarbonate polyol (such as bisphenol A polycarbonate polyol and / or bisphenol F polycarbonate polyol), whose hydroxyl value is in the range of 100-280mgKOH / g. H / g range (preferably 110-270 mgKOH / g, such as 120, 130, 140, 150, 180, 200, 220, 240, 250, 260); 5) 0.5-4 wt% (preferably 1-3.5 wt%, such as 1.5, 2, 2.5, 3 wt%) of a silane coupling agent containing a hydroxyl group or an amino group (e.g., a silane coupling agent containing 1, 2 or 3 hydroxyl groups or amino groups); wherein the weight percentage is based on the total amount of components 1)-5) (i.e., the sum of the percentages of components 1)-component 5) is 100 wt%);

[0025] (II) 1.5-6.5 parts by weight (preferably 1.8-6.0 parts by weight, such as 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 parts by weight) of a catalyst and a foam stabilizer as auxiliary agents; for example, the auxiliary agent includes 0.5-2.5 parts by weight (such as 1 or 1.5 or 2 parts by weight) of a catalyst, 1-4 parts by weight (such as 1.5, 2, 2.5, 3 or 3.5 parts by weight) of a foam stabilizer, relative to 100 parts by weight of the polymer polyol;

[0026] (III) 0-18 parts by weight of a flame retardant (as an auxiliary agent), more preferably 0-16 parts by weight, such as 4, 5, 6, 8, 10, 15, 17 parts by weight of a flame retardant, relative to 100 parts by weight of the polymer polyol;

[0027] (IV) 8-16 parts by weight (preferably 8.5-15.5 parts by weight, 9-15 parts by weight, 9.5-14.5 parts by weight, more preferably 10-14 parts by weight, preferably 10.5-13.5 parts by weight, preferably 11-13 parts by weight, such as 11.5, 12, 12.5 parts by weight) of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components:

[0028] (1) ethanol isopropanolamine (A1);

[0029] (2) ethanol diisopropanolamine (A2); and

[0030] (3) Water;

[0031] Wherein, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.1-9):1, preferably (0.15-8.5):1, preferably (0.2-8):1, preferably (0.3-7.5):1, preferably (0.4-7):1, preferably (0.5-6.5):1, preferably (0.6-6):1, preferably (0.7-5.5):1, preferably (0.8-5):1, preferably (0.9-4.5):1, preferably (1-4):1, preferably (1.2-3.8):1, preferably (1.4-3.6):1, preferably (1.5-3.5):1, preferably (1.7-3.3):1, preferably (1.8-3.2):1, preferably (2-3):1, preferably (2.2-2.8):1;

[0032] More preferably, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, preferably (0.6-3.8):1, preferably (0.7-3.7):1, preferably (0.8-3.6):1, preferably (1.0-3.5):1, preferably (1.1-3.3):1, preferably (1.5-3):1, preferably (1.7-2.8):1, preferably (2.0-2.6):1, preferably (2.2-2.4):1;

[0033] wherein the water content is 10-30wt%, preferably 11-29wt%, preferably 12-28wt%, preferably 13-27wt%, preferably 14-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, preferably 18-22wt%, based on the total weight of the alcoholamine composition (AC);

[0034] The total content of (A1) + (A2) + water is 90-100 wt %, preferably 92-100 wt %, preferably 93-100 wt %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 or 99.8 % or 99.9 %, based on the total weight of the alcoholamine composition (AC);

[0035] Wherein, a portion of the alkanolamines in the alkanolamine composition (AC) is neutralized by CO2 so that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0036] In the present application, catalysts, foam stabilizers and flame retardants serve as auxiliary agents.

[0037] Generally, the alcoholamine composition (AC) comprises the following components or consists of the following components or consists mainly of the following components:

[0038] (1) ethanol isopropanolamine (A1);

[0039] (2) ethanol diisopropanolamine (A2);

[0040] (3) Water;

[0041] (4) CO2;

[0042] (5) optional (optional) C2-C6 alcoholamine (A3) other than (A1) and (A2) (e.g. ethanolamine, isopropanolamine, diethanolamine, diisopropanolamine),

[0043] The total content of (A1) + (A2) + water + CO2 + (A3) is (approximately) 100 wt%, based on the total weight of the alcoholamine composition (AC).

[0044] That is, the alcoholamine composition (AC) further comprises (4) CO2 and (5) optionally a C2-C6 alcoholamine (A3) other than (A1) and (A2) (eg, ethanolamine, isopropanolamine, diethanolamine, diisopropanolamine).

[0045] As described above, when the total content of (A1) + (A2) + water is 90-100wt%, the content of CO2 and optional C2-C6 alcohol amine (A3) other than (A1) and (A2) is the remainder, i.e., 0-10wt% (for example, the content of CO2 is 0-6wt% or 1-6wt% or 2-5wt%; the content of (A3) can be 0-4wt% or 0-9wt% or 0-10wt% or 4-10wt% or 4-9wt% or 5-8wt%).

[0046] When the total content of (A1) + (A2) + water is 93-100wt% or 94-100wt%, the content of CO2 and optional C2-C6 alcohol amine (A3) other than (A1) and (A2) is the balance, i.e., 0-7wt% or 0-6wt% (for example, the content of CO2 is 0-7wt%, 0-6.5wt%, 0-6wt%, 1-6wt% or 2-5wt%; the content of (A3) can be 0-6wt% or 0-5wt% or 1-4wt%).

[0047] When the total content of (A1) + (A2) + water is 95-100wt%, the content of CO2 and optional C2-C6 alcohol amine (A3) other than (A1) and (A2) is the balance, i.e., 0-5wt% (for example, the content of CO2 is 0-5wt% or 1-5wt% or 2-4wt%; the content of (A3) is 0-5wt% or 0-4wt% or 1-3wt%).

[0048] And so on. For example, when the total content of (A1) + (A2) + water is 96-100wt%, the content of CO2 and optionally C2-C6 alcohol amine (A3) other than (A1) and (A2) is the balance, i.e., 0-4wt% (e.g., the content of CO2 is 0-4wt% or 1-4wt% or 2-3wt%; the content of (A3) is 0-4wt% or 0-3wt% or 1-2wt%). For example, when the total content of (A1) + (A2) + water is 97-100wt%, the content of CO2 and optionally C2-C6 alcohol amine (A3) other than (A1) and (A2) is the balance, i.e., 0-3wt% (e.g., the content of CO2 is 0-3wt% or 1-3wt%; the content of (A3) is 0-3wt% or 0-2wt%).

[0049] The C2-C6 alcoholamine (A3) other than (A1) and (A2) is ethanolamine, isopropanolamine, diethanolamine and / or diisopropanolamine; preferably, diethanolamine and / or diisopropanolamine.

[0050] Preferably, at an ambient temperature of 25°C, the CO2- and water-containing alkanolamine composition (AC) is in the form of a homogeneous liquid having a pressure of 200-1000 centipoise (25°C), preferably 250-900 centipoise (e.g. 300, 400, 500, 600, 700, 800 centipoise).

[0051] Preferably, the alcoholamine composition (AC) is prepared by the following preparation method:

[0052] 1) reacting ethanolamine with propylene oxide in the presence of water to obtain an ethanolamine composition (AC) containing ethanol diisopropanolamine (A2) and ethanol isopropanolamine (A1); wherein the molar ratio of propylene oxide to ethanolamine is (1.2-1.9):1, preferably (1.3-1.85):1, preferably (1.4-1.83):1, preferably (1.5-1.8):1; and the ethanolamine composition can be used in the next step without purification;

[0053] Wherein, the amount of water used in step 1) is such that the water content in the resulting alkanolamine composition (AC) is as defined above; for example, such that the water content in the alkanolamine composition (AC) is 10-30wt%, preferably 11-29wt%, preferably 12-28wt%, preferably 13-27wt%, preferably 14-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, preferably 18-22wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0054] 2) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining an alcoholamine composition (AC) containing CO2 and water;

[0055] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0056] Preferably, in the resulting alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 90-100 wt%, preferably 92-100%, preferably 94-100%, preferably 95-100%, preferably 96-100%, preferably 97-100%, preferably 98-100%, preferably 99-100%, such as 99.5%, 99.8%, 99.9%, based on the total weight of the alkanolamine composition (AC).

[0057] Alternatively, the alcoholamine composition (AC) is prepared by the following preparation method:

[0058] 1) Preparation of ethanol isopropanolamine: react ethanolamine with propylene oxide in the presence of water at a molar ratio of about (0.95-1.05):1 (e.g., about 1:1) to obtain ethanol isopropanolamine (A1); it can be used in the subsequent step 3) without purification;

[0059] 2) Preparation of ethanol diisopropanolamine: react ethanolamine with propylene oxide in the presence of water at a molar ratio of about 1:(1.9-2.1) (e.g., about 1:2) to obtain ethanol diisopropanolamine (A2); it can be used in the subsequent step 3) without purification;

[0060] 3) Preparation of an alcoholamine composition (AC): Mix the product of step 1) and the product of step 2), and optionally add water to obtain an alcoholamine composition (AC); wherein the amounts of ethanol diisopropanolamine (A2) and ethanol isopropanolamine (A1) are such that the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) in the obtained composition (AC) is as defined above, for example (0.1-9):1, preferably (0.15-8.5):1, preferably (0.2-8):1, preferably (0.3-7.5):1, preferably (0.4-7):1, preferably (0.5-6.5):1, preferably (0.6-6):1, preferably (0.7-5.5):1, preferably (0.8-5):1, preferably (0.9-4.5):1, preferably (1-4):1, preferably (1.2-3.8):1, preferably (1.4-3.6):1 , preferably (1.5-3.5):1, preferably (1.7-3.3):1, preferably (1.8-3.2):1, preferably (2-3):1, preferably (2.2-2.8):1; more preferably, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, Preferably (0.5-4):1, preferably (0.6-3.8):1, preferably (0.7-3.7):1, preferably (0.8-3.6):1, preferably (1.0-3.5):1, preferably (1.1-3.3):1, preferably (1.5-3):1, preferably (1.7-2.8):1, preferably (2.0-2.6):1, preferably (2.2-2.4):1; thereby obtaining an alcoholamine composition (AC);

[0061] Wherein, the total amount of water used in step 1) and step 2) should be such that the water content in the (final) obtained olamine composition (AC) is 10-30wt%, preferably 11-29wt%, preferably 12-28wt%, preferably 13-27wt%, preferably 14-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, preferably 18-22wt%, based on the total weight of the (final) olamine composition (AC);

[0062] Preferably, in the resulting alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 90-100 wt %, preferably 92-100 %, preferably 93-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 %, 99.8 %, 99.9 %, based on the total weight of the (final) alkanolamine composition (AC);

[0063] 4) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining a (final) alcoholamine composition (AC) containing CO2 and water;

[0064] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0065] Preferably, for the above-mentioned olamine composition (AC), the content of CO2 in the olamine composition (AC) is not higher than 7 wt% (more preferably not higher than 6.5 wt%, more preferably not higher than 6 wt%). If the content of CO2 in the olamine composition (AC) is higher than 7 wt%, this may cause the sprayed, cured polyurethane foam layer to often crack from the substrate (such as a stainless steel pipe or concrete) to form cracks or to crack between two adjacent foam layers to form cracks.

[0066] Preferably, the polyisocyanate is polymethyl polyphenyl polyisocyanate or MDI, preferably polymethyl polyphenyl polyisocyanate.

[0067] The inventors of the present application unexpectedly found that the aqueous alcoholamine composition (AC) of the present invention is a low-viscosity liquid at room temperature, which may be because ethanol isopropanolamine and ethanol diisopropanolamine have an asymmetric structure, are not easy to associate and crystallize, and are mixed with each other, resulting in the low viscosity of the alcoholamine composition (AC). Generally, the viscosity or dynamic viscosity (25°C) of the aqueous alcoholamine composition (AC) is 200-900 centipoise (mPa.s), preferably 220-800, more preferably 240-700, more preferably 250-600 centipoise, for example 280, 300, 400, 500, 650, 750 or 850 centipoise. For example, as a single compound, the freezing points (melting points) of diisopropanolamine and triisopropanolamine are 42° C. and 45° C., respectively, and at room temperature, diisopropanolamine and triisopropanolamine are white crystals or solid powders, which indicates that symmetrical diisopropanolamine and triisopropanolamine have a strong tendency to crystallize or associate. Therefore, in order to ensure that the alcoholamine composition (AC) of the present invention has a lower viscosity, it is desirable not to add diisopropanolamine and triisopropanolamine to the alcoholamine composition (AC) as much as possible.

[0068] Typically, the pH value of the alcoholamine composition (AC) containing alcoholamine partially neutralized by CO2 is in the range of 8-13.5, preferably 8-12, preferably 8.5-11.5, more preferably 9-11, preferably 9.1-10.5, preferably 9.2-10.

[0069] Actually, the aqueous alcoholamine composition (AC) of the present invention comprises alcoholamine carbonate+water+free alcoholamine, and therefore, it is a composite foaming agent with low viscosity.

[0070] In the present application, "optional" means with or without (0).

[0071] In addition, the inventors of the present application unexpectedly discovered that the above-mentioned aqueous alcohol amine composition (AC) of the present invention has good miscibility (or compatibility) in the dry white material formed by (I) polymer polyol and (II), and after being mixed, they can form a transparent, homogeneous and low-viscosity white material (i.e., a foaming polymer polyol composition for preparing polyurethane rigid foam).

[0072] The above-mentioned olamine composition (AC) of the present invention is directly used as a foaming agent for preparing polysiloxane-polyurethane rigid foam, and is particularly suitable for spraying polysiloxane-polyurethane foam, and is particularly suitable for winding spraying of polysiloxane-polyurethane foam on stainless steel pipes (e.g., with a diameter of 0.5-2 meters).

[0073] Preferably, for the above-mentioned olamine composition (AC), the CO2 content in the olamine composition (AC) is not higher than 7 wt% (more preferably not higher than 6.5 wt%, more preferably not higher than 6 wt%). If the CO2 content in the olamine composition (AC) is higher than 7 wt%, the wet foam sprayed onto the substrate (stainless steel or concrete) or onto the cured foam layer will expand rapidly and fall off the substrate; in addition, this may cause the sprayed, cured polyurethane foam layer to often crack from the substrate to form cracks or crack between two adjacent foam layers to form cracks.

[0074] Typically, the pH value of the alcoholamine composition (AC) in which the alcoholamine is partially neutralized by CO2 is in the range of 8-13.5, preferably 8.2-13, preferably 8.3-12, preferably 8.5-11.5, more preferably 9-11, preferably 9.1-10.5, preferably 9.2-10.

[0075] Actually, the aqueous alcoholamine composition (AC) of the present invention comprises alcoholamine carbonate+water+free alcoholamine, and therefore, it is a composite foaming agent with low viscosity.

[0076] In the present application, "optional" means with or without (0).

[0077] In addition, the inventors of the present application have found that the above-mentioned aqueous alcohol amine composition (AC) (IV) of the present invention has good miscibility (or compatibility) in the dry white material formed by (I) polymer polyol and (II)-(III) additives, and after being mixed, they can form a transparent, homogeneous and low-viscosity white material (i.e., a foaming polymer polyol composition for preparing polyurethane rigid foam).

[0078] The above-mentioned alcohol amine composition (AC) of the present invention is directly used as a foaming agent for preparing polysiloxane-polyurethane rigid foam, and is particularly suitable for spraying polysiloxane-polyurethane rigid foam.

[0079] The thermal conductivity λ (w / m·k, 20°C) of the spray polysiloxane-polyurethane rigid foam of the present invention is generally lower than 0.02245, preferably lower than 0.02240, more preferably lower than 0.02235, more preferably lower than 0.02230, more preferably lower than 0.02220, more preferably lower than 0.02210, more preferably lower than 0.02205.

[0080] The compressive strength of the spray polyurethane rigid foam of the present invention (in the direction perpendicular to the substrate, for example, when the density of the foam is about 38-40 Kg / cm 3 ) is 345-360 (KPa), preferably 350-358 (KPa).

[0081] Advantages of the present invention

[0082] 1. The olamine composition (AC) of the present invention does not crystallize or solidify at ambient temperature (e.g., 5-40° C.) and has a low viscosity, and can be uniformly mixed in a polymer polyol composition (white material) for foaming, and can thus be uniformly foamed to form a foam material with uniform cell size.

[0083] 2. In the prior art, if a polyether polyol composition with high reactivity is used in a large amount and a foaming agent composition (or amine composition) with a high CO2 content is used, the reaction is too rapid in the early stage of the foaming reaction (the reaction system has not yet fully gelled) during the spraying operation, and the foaming agent composition (or amine composition) with a high CO2 content is heated and quickly releases a large amount of CO2 gas, causing the wet foam sprayed onto the (stainless steel or concrete) substrate or onto the cured foam layer to expand rapidly and fall off the substrate. In addition, the cured foam has high brittleness, so it shrinks and deforms slightly, resulting in cracks between the cured foam material and the substrate or between two adjacent cured foam layers. These problems are particularly prominent when spraying in cold winter.

[0084] The present invention can overcome the foam cracking problem by using a foaming agent olamine composition with a specific CO2 content and a specific polymer polyol. In the olamine composition (AC) of the present invention, only a portion of the olamine is neutralized by CO2. In addition, by selecting a specific polymer polyol 1)-4), the foam cracking phenomenon often encountered when using an olamine composition with a higher CO2 content as a foaming agent and other highly reactive polyether polyol compositions in the prior art can be avoided during the foam spraying process.

[0085] 3. There are almost no small molecular compounds in the sucrose-started polyether polyol (preferably sucrose-started polyoxypropylene polyol) and it has a suitable hydroxyl value, so the prepared foam has low brittleness. The sorbitol-started polyether polyol (preferably sorbitol-started polyoxypropylene polyol) has good compatibility with the chemical foaming agent (AC) and has a suitable hydroxyl value, which is conducive to the formation of fine pores. By using polysiloxane diol, polycarbonate polyol and silane coupling agent, the mechanical strength, bonding strength to (inorganic) substrates (concrete or steel), hydrolysis resistance, thermal stability and weather resistance of the obtained polysiloxane-polyurethane foam can be improved.

[0086] 4. Compared with the salts of alcohol amines with two or three carbon atoms (diethanolamine carbonate and diisopropanolamine carbonate), the reaction activity and urethanization catalysis of ethanol carbonate isopropanolamine salt and ethanol carbonate diisopropanolamine salt are lower, making the foaming process smoother. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 is a SEM photograph of the foam of Example 1.

[0088] Figure 2 This is a SEM photograph of the foam of Example 2.

[0089] Figure 3 This is a SEM photograph of the foam of Example 3.

[0090] Figure 4 This is a SEM photograph of the foam of Example 4.

[0091] Figure 5 is a SEM photograph of the foam of Comparative Example 1.

[0092] Figure 6 is a photograph of a cross section of the foam of Comparative Example 1.

[0093] Figure 7 is a SEM photograph of the foam of Comparative Example 2.

[0094] Figure 8 The product of Preparation Example 2 1 H-NMR spectrum.

[0095] Fig. 9 The product of Preparation Example 3 1 H-NMR spectrum.

[0096] Reference numerals: 2: crack (delamination) between two adjacent foam layers; 3: substrate (cement board). DETAILED DESCRIPTION

[0097] The present invention further illustrates the technical solution through the following examples, but the present invention is not limited to these examples.

[0098] Unless otherwise specified, the devices used in the examples are all devices commonly used in the art and commercially available on the market.

[0099] Method for measuring the content of alcoholamines: In the embodiments, the method for measuring the content of various alcoholamines (e.g., ethanol isopropanolamine, ethanol diisopropanolamine) in the aqueous alcoholamine mixture (AC) (or aqueous alcoholamine composition or alcoholamine hydrate) can be performed by gas chromatography, wherein the gas chromatograph is equipped with a hydrogen flame ionization detector (FID), and the mass concentration of the alcoholamine compound is about 10 mg / mL, which is a standard solution. Gas chromatography conditions: HP-5 capillary column (30m×0.32mm id×0.25μm, 5% phenyl methyl-siloxane); the column temperature was programmed, the initial temperature was 80℃, maintained for 3min, then increased to 250℃ at a rate of 25℃ / min, and maintained for 5min; the injection port temperature was 250℃; the detector temperature was 260℃; the carrier gas was high-purity nitrogen with a flow rate of 1.5mL / min; the fuel gas was hydrogen with a flow rate of 30mL / min; the auxiliary gas was air with a flow rate of 300mL / min; the tail gas was nitrogen with a flow rate of 25mL / min; the injection method was split injection, with a split ratio of 30:1; the injection volume was 1μL.

[0100] In the present application, as a sucrose-started polyether polyol having a hydroxyl value between 290 and 450 mg KOH / g, polyether polyol 8310 (sucrose initiator, hydroxyl value 310 mg KOH / g) of BEFAR GROUP CO., LTD., polyether polyol H4110S (hydroxyl value 400-420 mg KOH / g) and H4520 (hydroxyl value 335-365 mg KOH / g) of Hongbaoli Group Co., Ltd., and polyether polyol YD-8238 (hydroxyl value 385 ± 10 mg KOH / g) and YD-889 (hydroxyl value 405 ± 10 mg KOH / g) of Hebei Yadong Chemical Group Co., Ltd. can be used.

[0101] As polysiloxane diols having a hydroxyl equivalent weight (HEW) between 400 and 600 g / mol (e.g., polydimethylsiloxane diol), hydroxyl-terminated polysiloxanes MCR-C61 (hydroxyl equivalent weight HEW = 500 g / mol, functionality 2) and MCR-62 (hydroxyl equivalent weight 2500 g / mol, functionality 2) from Gelest, USA, and Silmer OH Di-100 (hydroxyl equivalent weight 3500 g / mol, functionality 2) from Sil TECH can be used. In addition, other polysiloxanes for rigid polyurethane foams can also be used, such siloxanes include B 8465, B8462, B ​​8467, B 8461, B8516, B 8476 produced by Degussa, L-6900, L-6910, L-6915, L-6920, L-6980, L-5440 produced by Crompton, SS8005, SS8002 produced by Saxol, DC5950, DC193, DC1598 produced by Air Products, etc.

[0102] As the sorbitol-started polyether polyol with a hydroxyl value between 340 and 520 mgKOH / g, polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g) of Jiahua Chemical Co., Ltd., polyether polyol H5021 (hydroxyl value 355-385 mgKOH / g) and H635SG (hydroxyl value 485-515 mgKOH / g) of Hongbaoli Group Co., Ltd., and polyether polyol YD-635 (hydroxyl value 490±15 mgKOH / g) and YD-6205 (hydroxyl value 380±15 mgKOH / g) of Hebei Yadong Chemical Group Co., Ltd. can be used.

[0103] As the polycarbonate polyol having a hydroxyl value of 100-280 mgKOH / g, SYHP1000 polycarbonate polyol produced by Shanghai Shuyu Chemical Co., Ltd. and bisphenol A type polycarbonate polyol produced by Hubei Chengfeng Chemical Co., Ltd. can be used.

[0104] As the silane coupling agent containing a hydroxyl group or an amino group, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.), N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792,), and 3-aminopropyltriethoxysilane (KH-550) can be used.

[0105] Commonly used catalysts are selected from: 33LV (A-33): 33% triethylenediamine in dipropylene glycol solution, N,N-dimethylethanolamine, N,N-dimethylbenzylamine, 70% bis(dimethylaminoethyl) ether in dipropylene glycol solution, 70% potassium octoate in diethylene glycol solution, dibutyltin dilaurate, PT303, PT304, potassium acetate, PC-8 (N,N-dimethylcyclohexylamine), PC-5 (N,N,N,N,N-pentamethyldiethylenetriamine), PC-41 (tris(dimethylaminopropyl)hexahydrotriazine), triethanolamine, JXP-508, JXP-509, TMR-2 (2-hydroxy-N,N,N-trimethyl-1-propylamine formate, Air Products and Chemicals, USA), TMR-3, TMR-4, Dabco 2040 (Evonik Chemicals). Commonly used silicone oil foam stabilizers or silane surfactants: B8525 and B8408 of Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 of Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 of Gas & Chemicals, and silicone oil 8841 of Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 of Gas & Chemicals. Commonly used flame retardants: flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), TCPP (Qingdao Lianmei Chemical Co., Ltd.), TCEP, DMMP, ammonium chloride, aluminum hydroxide powder, DM1201, DM1301, tetrabromophthalic anhydride diol.

[0106] The following describes a method for preparing an amine carbonate chemical foaming agent (i.e., an amine carbonate hydrate) by CO2 aeration.

[0107] The water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method = the amount of free water in the hydrate + the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate. Therefore, the content of free water (wt%) in the carbonate ethanolamine salt chemical blowing agent (F1) (i.e., carbonate ethanolamine salt hydrate) = (the water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method) - (the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate). For example, the water content in the alcoholamine composition (AC) described in the present application refers to the water content measured by the Karl Fischer method.

[0108] The test methods for various parameters of polyurethane rigid foam are carried out with reference to the following Chinese national standards GB:

[0109]

[0110] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the substrate), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.

[0111] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 30°C.

[0112] Preparation Example 1

[0113] Part I: Preparation of single alcohol amines

[0114] 1) 36.6 kg of ethanolamine (molecular weight 61,600 mol) and 16.7 kg of deionized water were added to an autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C. and the pressure was controlled to be no higher than 0.3 MPa. 34.8 kg of propylene oxide (molecular weight 58,600 mol, the molar ratio of propylene oxide to ethanolamine was 1:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 88 kg of the reaction product (alkanolamine hydrate AA1a) was discharged from the reactor. The product was sampled and the content of ethanol isopropanolamine in the alkanolamine hydrate AA1a was measured by gas chromatography to be 599.7 mol and 0.3 mol of ethanol diisopropanolamine. Its viscosity (30° C.) was 283 centipoise. The water content in the alkanolamine hydrate AA1a was 18.9 wt%. The pH value was 12.43.

[0115] 2) 30.5 kg of ethanolamine (molecular weight 61,500 mol) and 20.58 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95 ° C, and the pressure was controlled to be no higher than 0.3 MPa. 58 kg of propylene oxide (1000 mol, the molar ratio of propylene oxide to ethanolamine was 2:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40 ° C. Then, 109 kg of the reaction product (alkanolamine hydrate AAxa) was discharged from the reactor, and a sample was taken from the product and the content of ethanol diisopropanolamine in the alkanolamine hydrate AAxa was measured by gas chromatography to be 499.7 mol, and the content of ethanol isopropanolamine was 0.3 mol. Its viscosity (25 ° C) was 390 centipoise. The water content in the alkanolamine hydrate AAxa was 18.8 wt%. pH value = 11.72.

[0116] Part 2: Compounding

[0117] 1) 4 batches of 20 kg each were taken from 88 kg of the reaction product (alcoholamine hydrate AA1a). For each batch, 20 kg of the reaction product (alcoholamine hydrate AA1a, 136.3 mol of ethanol isopropanolamine) was added to a high-pressure reactor, and then alkanolamine hydrate AAxa (water content of 18.8 wt%) and water were added, and the mixture was mixed according to the molar ratio and water content in Table 1 below to obtain four batches of alkanolamine compositions AC (AA1b-AA1e).

[0118] 2) In addition, the remaining 8 kg of the reaction product (alcoholamine hydrate AA1a) was added to the autoclave, and then the alcoholamine hydrate AAxa containing ethanol diisopropanolamine (water content of 18.8 wt%) and water were added and mixed according to the molar ratio and water content in the following Table 1 to obtain the fifth batch of alcoholamine composition AC (AA1f).

[0119] Table 1: Molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine

[0120]

[0121] Part 3: CO2 Neutralization and Salt Formation

[0122] The four batches of amine hydrates AA1b-AA1e obtained by the above blending and the fifth batch of amine hydrates AA1f were added to the autoclave respectively, and carbon dioxide gas was introduced into the amine hydrates AA1b-AA1e and AA1f respectively under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be no higher than 0.3MPa, and the temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours, and the pressure was released after the temperature was lowered to below 40°C, and then a small amount of water was added to make the water content in the carbonate alcohol amine salt composition reach about 19.5wt%, and the mixture was slowly stirred for 30 minutes, and the product was discharged, thereby obtaining carbonate alcohol amine salt compositions AA2b-AA2f (or carbonate alcohol amine salt compositions 1-5). The CO2 content is shown in Table 2.

[0123] Table 2: CO2 content in carbonate amine salt compositions

[0124]

[0125] As the CO2 content is higher than 5%, the viscosity of the alcohol amine composition AC increases rapidly. When the CO2 content is low (e.g., lower than 4 wt%), the content of ethanol diisopropanolamine mainly affects the viscosity of the carbonate alcohol amine salt composition AC, while when the CO2 content is higher than 5%, the CO2 content has a greater impact on the viscosity of the carbonate alcohol amine salt composition AC.

[0126] Preparation Example 2

[0127] 24.64 kg of ethanolamine (molecular weight 61, 404 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.64 kg of the reaction product (alcoholamine hydrate AA3a, or alcoholamine composition AA3a) was discharged from the reactor, and the viscosity (25° C.) was 288 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA3a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.9 mol, the content of ethanol diisopropanolamine was 323.1 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 8 The water content of the alcoholamine hydrate AA3a was determined by Karl Fischer method to be 15.6 wt %.

[0128] Then, 40kg of the above obtained alcoholamine hydrate AA3a is added to the autoclave, and carbon dioxide gas is introduced into the alcoholamine hydrate AA3a under the condition that the pressure of the CO2 gas outputted from the CO2 storage cylinder is not higher than 0.3MPa, and the temperature is controlled between 40-50°C, and the temperature control reaction is performed for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcoholamine salt composition AA3b (or referred to as alcoholamine composition AA3b), wherein the CO2 absorption capacity is 440g (about 10mol, i.e., 9.7mol% of the alcoholamine in AA3a is neutralized by CO2 to form carbonate alcoholamine salt; CO2 content is 1.088wt%). The dynamic viscosity (25°C) of the product AA3b is 395 centipoise. The pH of the product AA3b measured by a pH meter (Ray Magnetic PHS-3C type, Shanghai Yidian Science Instrument Co., Ltd.) is 11.4. Its decomposition temperature is between 45℃ and 60℃.

[0129] Preparation Example 3

[0130] 17.64 kg of 1,4-diamine (molecular weight 88.15, 200 mol) and 9.2 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.3 MPa. 23.232 kg of propylene oxide (molecular weight 58.079, 400 mol) was added to the reactor in batches. After the addition, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40°C. Then, about 50 kg of the reaction product (alcoholamine hydrate AA4a) was discharged from the reactor, and the pH value of the product measured by a pH meter was 13.46. Samples were taken from the product and the content of N,N,N'-tri(hydroxyisopropyl)-diamine in the alcoholamine hydrate AA4a was measured by gas chromatography to be about 0.02 mol, and the content of N,N'-di(hydroxyisopropyl)-diamine was about 199.98 mol. Its viscosity (25°C) is 324 centipoise. The water content of the alcoholamine hydrate AA4a measured by Karl Fischer method is 18.4 wt%. A sample is taken from the obtained product for testing NMR spectrum. 1 H-NMR shows Fig. 9 . Fig. 9 It is shown that the product of Preparation Example 3 is N,N'-di(hydroxyisopropyl)-butylene diamine. This shows that the alcohol amine product obtained by the reaction of organic amine and epoxide depends on the molar ratio of organic amine to epoxide. This alcohol amine product can also be used as a component of PU foaming agent.

[0131] Application Examples

[0132] Example 1

[0133] 1. Raw materials of white material component: 55 kg of polyether polyol 8310 (sucrose initiator, hydroxyl value 310 mg KOH / g, BEFAR GROUP CO., LTD.), 22 kg of hydroxyl-terminated polysiloxane MCR-C61 (hydroxyl equivalent HEW = 500 g / mol, functionality 2, Gelest Company, USA), 15 kg of polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g, BEFAR GROUP CO., LTD.) KOH / g, Jiahua Chemical Co., Ltd.), 7kg polycarbonate polyol (SYHP1000, Shanghai Shuyu Chemical Co., Ltd.), 1kg of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.), 1kg catalyst TMR-2 (Air Chemicals, USA), 0.1kg catalyst Dabco2040 (Evonik Chemical), 1.5kg foam stabilizer DC3201 (Gas and Chemicals Company), 15kg flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 10kg of carbonate amine salt composition 1 (AA2b) in Preparation Example 1 (wherein, the molar ratio of triolamine (A2) (ethanol diisopropanolamine) to diolamine (A1) (ethanol isopropanolamine) is 4:1, and the CO2 content is 3.6wt%).

[0134] 2. Add weighed polyether polyol 8310, polysiloxane MCR-C61, polyether polyol 8038, polycarbonate polyol SYHP1000, silane coupling agent YJ-602, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate amine salt composition 1 (AA2b) into the reactor in sequence, and stir slowly (180 rpm) for 2 hours at room temperature to mix them thoroughly to obtain a uniform, transparent mixture (i.e., the white material component).

[0135] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0136] 4. At an ambient temperature of 25°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 25°C by a Graco sprayer A-25. The foam was sprayed in a spraying manner with each layer of foam being 2-3cm thick and the total foam thickness being 20cm. During the spraying process, no phenomenon of wet foam falling off in the form of large-sized flakes or blocks was observed. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 3. The SEM photograph of the foam material sample is shown in Figure 1 The cell size of the foam is very uniform. No delamination between adjacent foam layers was found in the cured foam.

[0137] Example 2

[0138] Example 1 was repeated, except that the same amount of the carbonate alcohol amine composition 2 (AA2c) of the preparation example (wherein the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) was 1:1, and the CO2 content was 4.1 wt%) was used instead of the carbonate alcohol amine salt composition 1 (AA2b) to prepare a polyurethane rigid foam material. The SEM photograph of the foam material is shown in Figure 2 The cell size is very uniform. During the spraying process, no large-sized flakes or blocks of wet foam were observed to fall off, and no delamination between adjacent foam layers was found in the cured foam.

[0139] Example 3

[0140] Example 1 was repeated except that the same amount of the carbonate alcohol amine composition 3 (AA2d) of the preparation example (wherein the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) was 0.5:1, and the CO2 content was 5.0 wt%) was used instead of the carbonate alcohol amine salt composition 1 (AA2b) to prepare a polyurethane rigid foam material. The SEM photograph of the foam material is shown in Figure 3 The cell size is uniform. No phenomenon of wet foam falling off in the form of larger flakes or blocks was observed during the spraying process, and no delamination between adjacent foam layers was found in the cured foam.

[0141] Example 4

[0142] Example 1 was repeated except that the same amount of the carbonate alcohol amine composition 4 (AA2e) of the preparation example (wherein the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) was 0.25:1, and the CO2 content was 5.6 wt%) was used instead of the carbonate alcohol amine salt composition 1 (AA2b) to prepare a polyurethane rigid foam material. The SEM photograph of the foam material is shown in Figure 4 The cell size is uniform. No phenomenon of wet foam falling off in the form of larger flakes or blocks was observed during the spraying process, and no delamination between adjacent foam layers was found in the cured foam.

[0143] Comparative Example 1

[0144] The operation process is repeated in Example 1, except that the same amount of the carbonate amine salt composition 5 (AA2f) of the preparation example (wherein the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is 0.25:1, and the CO2 content is 7.6wt%) is used instead of the carbonate amine salt composition 1 (AA2b).

[0145] 1. Raw materials of white material component: 55 kg of polyether polyol 8310 (sucrose initiator, hydroxyl value 310 mg KOH / g, BEFAR GROUP CO., LTD.), 22 kg of hydroxyl-terminated polysiloxane MCR-C61 (hydroxyl equivalent HEW = 500 g / mol, functionality 2, Gelest Company, USA), 15 kg of polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g, BEFAR GROUP CO., LTD.) KOH / g, Jiahua Chemical Co., Ltd.), 7kg polycarbonate polyol (SYHP1000, Shanghai Shuyu Chemical Co., Ltd.), 1kg of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.), 1kg catalyst TMR-2 (Air Chemicals, USA), 0.1kg catalyst Dabco2040 (Evonik Chemical), 1.5kg foam stabilizer DC3201 (Gas and Chemicals Company), 15kg flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 10kg of carbonate amine salt composition 5 (AA2f) in Preparation Example 5 (wherein the molar ratio of triolamine (A2) (ethanol diisopropanolamine) to diolamine (A1) (ethanol isopropanolamine) is 0.25:1, and the CO2 content is 7.6wt%).

[0146] 2. Add weighed polyether polyol 8310, polysiloxane MCR-C61, polyether polyol 8038, polycarbonate polyol SYHP1000, silane coupling agent YJ-602, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate amine salt composition 5 (AA2f) into the reaction kettle in sequence, and stir slowly (180 rpm) for 2 hours at room temperature to mix them thoroughly to obtain a uniform, transparent mixture (i.e., the white material component).

[0147] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0148] 4. At an ambient temperature of 25°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 25°C by a Graco sprayer A-25. The foam was sprayed in a spraying manner with each layer of foam being 2-3cm thick and the total foam thickness being 20cm. During the spraying process, it was observed that the wet foam fell in the form of larger blocks. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 3. The SEM photos of the foam material samples are shown in Figure 5 . The cell size is somewhat uniform.

[0149] The solidified polyurethane foam on the cement board (substrate) was cut open with an electric saw and the cross section was observed. It was found that cracks were formed by delamination between two adjacent foam layers. Figure 6 as shown in .

[0150] The results of Comparative Example 1 show that when a polyether polyol with a higher activity and a carbonate alcohol amine salt composition with a higher CO2 content are used, the wet foam is observed to fall off in the form of larger blocks during the spraying process, and for the cured foam, delamination and cracking between adjacent foam layers are found (such as Figure 6 However, the bonding strength between the foam and the cement board substrate is better (probably due to the addition of silane coupling agent).

[0151] Comparative Example 2

[0152] Example 1 was repeated, except that 22 kg of pentaerythritol-based polyether polyol H8404 (hydroxyl value 435-465 mgKOH / g, Hongbaoli Group Co., Ltd.) was used instead of 22 kg of hydroxyl-terminated polysiloxane MCR-C61, and 8 kg of glycerol-based polyether polyol H305 (hydroxyl value 320-350 mgKOH / g, Hongbaoli Group Co., Ltd.) was used instead of 7 kg of polycarbonate polyol (SYHP1000, Shanghai Shuyu Chemical Co., Ltd.) and 1 kg of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.). A polyurethane rigid foam material was obtained. The SEM photograph of the foam material is shown in Figure 7 The cell size is very uniform. The performance parameters of the obtained foam product are listed in Table 3.

[0153] Therein, no phenomenon of wet foam falling off in the form of larger-sized flakes or blocks was observed during the spraying process, and no delamination between adjacent foam layers was found in the solidified foam.

[0154] Table 3 - Performance parameters of foam materials

[0155]

[0156] Note: The compressive strength is measured for the foam specimen in the Z direction (perpendicular to the substrate), and "delamination" means that cracks are formed by delamination between two adjacent foam layers. "Slightly uniform" means that the cell size is moderately uniform.

[0157] As can be seen from Table 3 above, when the carbonate amine salt composition (AC) with a specific CO2 content of the present invention is used as a chemical foaming agent in combination with a specific combined polyether polyol, there is no drop of wet foam during the spraying process, and the prepared polyurethane rigid foam material has excellent overall performance, stable size, low thermal conductivity and good thermal insulation performance.

[0158] Compared with Comparative Example 2 (using a combined polyether), Example 1 has higher compressive strength and better dimensional stability (70°C) (lower value), which indicates that the use of polysiloxane diol, polycarbonate polyol and silane coupling agent is beneficial to improving the strength and heat resistance of polyurethane foam.

Claims

1. A polysiloxane-polyurethane rigid foam, which is formed by mixing and spraying a polyisocyanate with a polymer polyol composition, wherein the polymer polyol composition comprises or consists of the following components: (I) 100 parts by weight of a polymer polyol, comprising: 1) 50-60 wt% of a sucrose-based polyether polyol having a hydroxyl value in the range of 290-450 mgKOH / g; 2) 20-25 wt% of a polysiloxane diol having a hydroxyl equivalent weight (HEW) in the range of 400-600 g / mol; 3) 12-18 wt% of a sorbitol-based polyether polyol having a hydroxyl value in the range of 340-520 mgKOH / g; 4) 5-10 wt% of a polycarbonate polyol having a hydroxyl value in the range of 100-280 mgKOH / g; 5) 0.5-4 wt% of a silane coupling agent containing a hydroxyl group or an amino group; wherein the weight percentages are based on the total amount of components 1) to 5); (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer relative to 100 parts by weight of the polymer polyol; (III) 0-18 parts by weight of a flame retardant relative to 100 parts by weight of the polymer polyol; (IV) 8-16 parts by weight of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components: (1) ethanol isopropanolamine (A1); (2) ethanol diisopropanolamine (A2); and (3) Water; Wherein, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.1-9):1; wherein the content of water is 10-30 wt %, based on the total weight of the alcoholamine composition (AC); The total content of (A1) + (A2) + water is 90-100 wt %, based on the total weight of the alcoholamine composition (AC); Wherein, a portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1-7 wt% based on the total weight of the alcoholamine composition (AC).

2. The polysiloxane-polyurethane rigid foam according to claim 1, wherein: The polymer polyol comprises: 1) 52-58 wt% of sucrose-based polyether polyol; 2) 21-23 wt% of polysiloxane diol; 3) 13-17 wt% of sorbitol-based polyether polyol; 4) 6-9 wt% of polycarbonate polyol; and 5) 1-3.5 wt% of a silane coupling agent containing a hydroxyl group or an amino group. wherein the weight percentages are based on the total amount of components 1)-5); and / or The amount of component (II) auxiliary agent is 2.5-5 parts by weight, including 1-2 parts by weight of catalyst and 1.5-3 parts by weight of foam stabilizer; and / or The flame retardant of component (III) is used in an amount of 4 to 16 parts by weight relative to 100 parts by weight of the polymer polyol; and / or The amount of component (IV) olamine composition (AC) is 9-15 parts by weight, and the water content in the olamine composition (AC) is 12-28 wt %; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.5-6.0 wt%; and / or The total content of (A1)+(A2)+water is 93-100 wt %, based on the total weight of the alcoholamine composition (AC).

3. The polysiloxane-polyurethane rigid foam according to claim 1 or 2, wherein: 1) The hydroxyl value of the sucrose-based polyether polyol is in the range of 310-430 mgKOH / g; 2) The hydroxyl equivalent weight (HEW) of the polysiloxane diol is in the range of 440-560 g / mol; 3) The hydroxyl value of the sorbitol-based polyether polyol is in the range of 350-490 mgKOH / g; 4) The hydroxyl value of the polycarbonate polyol is in the range of 120-260 mgKOH / g; and / or In the alcoholamine composition (AC), the water content is 12-28 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2-5.0 wt%; and / or The amount of component (IV) olamine composition (AC) is 10-14 parts by weight relative to 100 parts by weight of polymer polyol; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-5):1; and / or The total content of (A1)+(A2)+water is 94-100 wt %, based on the total weight of the alkanolamine composition (AC).

4. The polysiloxane-polyurethane rigid foam according to claim 3, wherein: In the alcoholamine composition (AC), the water content is 14-26 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 3-5 wt%; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.25-4):1; and / or The total content of (A1)+(A2)+water is 95-100 wt %, based on the total weight of the alcoholamine composition (AC).

5. The polysiloxane-polyurethane rigid foam according to claim 4, wherein: In the alcoholamine composition (AC), the water content is 15-25 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized with CO2 so that the CO2 content in the alcoholamine composition (AC) is 3.5-4 wt%; and / or The total content of (A1) + (A2) + water is 96-100 wt %, based on the total weight of the alcoholamine composition (AC); and / or When the density of the foam is 38-40Kg / cm 3 When the foam is subjected to pressure drop, the compressive strength of the foam is 345-360 (KPa), preferably 350-358 (KPa).

6. A method for preparing a polysiloxane-polyurethane rigid foam according to any one of claims 1 to 5, the method comprising mixing and spraying a polyisocyanate with a polymer polyol composition, wherein the polymer polyol composition comprises or consists of the following components: (I) 100 parts by weight of a polymer polyol, comprising: 1) 50-60 wt% of a sucrose-based polyether polyol having a hydroxyl value in the range of 290-450 mgKOH / g; 2) 20-25 wt% of a polysiloxane diol having a hydroxyl equivalent weight (HEW) in the range of 400-600 g / mol; 3) 12-18 wt% of a sorbitol-based polyether polyol having a hydroxyl value in the range of 340-520 mgKOH / g; 4) 5-10 wt% of a polycarbonate polyol having a hydroxyl value in the range of 100-280 mgKOH / g; 5) 0.5-4 wt% of a silane coupling agent containing a hydroxyl group or an amino group; wherein the weight percentages are based on the total amount of components 1) to 5); (II) 1.5-6.5 parts by weight of a catalyst and a foam stabilizer relative to 100 parts by weight of the polymer polyol; (III) 0-18 parts by weight of a flame retardant relative to 100 parts by weight of the polymer polyol; (IV) 8-16 parts by weight of a CO2- and water-containing olamine composition (AC) as a blowing agent, relative to 100 parts by weight of the polymer polyol; the olamine composition (AC) comprises or consists of or is mainly composed of the following components: (1) ethanol isopropanolamine (A1); (2) ethanol diisopropanolamine (A2); and (3) Water; Wherein, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.1-9):1; wherein the content of water is 10-30 wt %, based on the total weight of the alcoholamine composition (AC); The total content of (A1) + (A2) + water is 90-100 wt %, based on the total weight of the alcoholamine composition (AC); Wherein, a portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1-7 wt% based on the total weight of the alcoholamine composition (AC).

7. The method according to claim 6, wherein: The polymer polyol comprises: 1) 52-58 wt% of sucrose-based polyether polyol; 2) 21-23 wt% of polysiloxane diol; 3) 13-17 wt% of sorbitol-based polyether polyol; 4) 6-9 wt% of polycarbonate polyol; 5) 1-3.5 wt% of a silane coupling agent containing a hydroxyl group or an amino group; wherein the weight percentages are based on the total amount of components 1) to 5); and / or The amount of component (II) auxiliary agent is 2.5-5 parts by weight, including 1-2 parts by weight of catalyst and 1.5-3 parts by weight of foam stabilizer; and / or The flame retardant of component (III) is used in an amount of 4 to 16 parts by weight relative to 100 parts by weight of the polymer polyol; and / or The amount of component (IV) olamine composition (AC) is 9-15 parts by weight, and the water content in the olamine composition (AC) is 12-28 wt %; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.5-6.0 wt%; and / or The total content of (A1)+(A2)+water is 93-100 wt %, based on the total weight of the alcoholamine composition (AC).

8. The method according to claim 6 or 7, wherein: 1) The hydroxyl value of the sucrose-based polyether polyol is in the range of 310-430 mgKOH / g; 2) The hydroxyl equivalent weight (HEW) of the polysiloxane diol is in the range of 440-560 g / mol; 3) The hydroxyl value of the sorbitol-based polyether polyol is in the range of 350-490 mgKOH / g; 4) The hydroxyl value of the polycarbonate polyol is in the range of 120-260 mgKOH / g; and / or In the alcoholamine composition (AC), the water content is 12-28 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2-5.0 wt%; and / or The amount of component (IV) olamine composition (AC) is 10-14 parts by weight relative to 100 parts by weight of polymer polyol; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-5):1; and / or The total content of (A1)+(A2)+water is 94-100 wt %, based on the total weight of the alkanolamine composition (AC).

9. The method according to claim 8, wherein: In the alcoholamine composition (AC), the water content is 14-26 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 3-5 wt%; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.25-4):1; and / or The total content of (A1)+(A2)+water is 95-100 wt %, based on the total weight of the alcoholamine composition (AC).

10. The method according to claim 9, wherein: In the alcoholamine composition (AC), the water content is 15-25 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized with CO2 so that the CO2 content in the alcoholamine composition (AC) is 3.5-4 wt%; and / or The total content of (A1) + (A2) + water is 96-100 wt %, based on the total weight of the alcoholamine composition (AC); and / or The polyisocyanate is polymethyl polyphenyl polyisocyanate.

Citation Information

Patent Citations

  • Process for separating components from ethanolamine mixtures

    CA1003358A

  • Novel preparation method for mono ethanol diisopropanolamine

    CN103435499A

  • Monoethanol diisopropanol amine production method

    CN107663157A

  • Foaming agent containing secondary amine salts and propanol amine salts and application for foam material of polyurethane refrigerators and freezers

    CN109422903A

  • Foaming agent comprising polyamine salt and propanolamine salt and use for polyurethane refrigerator foam material

    CN109422913A